Formal intergenerational mentoring at Australian Men's Sheds: a targeted survey about mentees, mentors, programmes and quality. (18th August 2015) - Cordier, Reinie; Wilson, Nathan J.; Stancliffe, Roger J.; MacCallum, Judith; Vaz, Sharmila; Buchanan, Angus; Ciccarelli, Marina; Falkmer, Torbjorn S.
Abstract: Intergenerational mentoring enables a purposeful exchange of skills and knowledge to enhance individual and social outcomes for sub‐groups at risk of health and social disparities. Male intergenerational mentoring may be an approach to help address these disparities in young men. Over 1000 Men's Sheds operate in Australia with 39% providing some form of mentoring mainly to youth. Yet, little is known about the variables intrinsic to creating and running quality programmes. This study aimed to identify the characteristics of formal intergenerational mentoring programmes, review their quality against the Australian Youth Mentoring Network (AYMN) quality benchmarks, and identify the factors that predict quality in these programmes. All known Australian Men's Sheds were invited to participate in an online cross‐sectional survey. Forty sheds with formal mentor programmes completed the survey for a total of 387 mentees (mean = 9.7 mentees/programme), the majority being male. The majority of mentor programme facilitators were unpaid male volunteers aged 61 years and older, and programmes were unfunded. Promoting social and emotional well‐being of the mentees was the primary focus in more than half of the programmes, and working on a shared construction project was the most common activity. Respondents rated the three most important factors that influenced programme effectiveness as being: (i) meaningful activities; (ii) mentors' approach; and (iii) a safe environment. Univariate analyses revealed that mentoring programmes that had a system in place for screening mentors, trained mentors and evaluated the programme were most likely to rate highly against the AYMN quality benchmarks.